The ruins as museum of the place’s palimpsest. The ABDR’s project for the Mausoleum of Augustus - Rachele Lomurno (Festival dell'Architettura Magazine, 2020)
In the stratified Mediterranean cities the archaeological ruins re-emerge in a context deeply changed from the one they belonged to and lead us in ancient times, whose memory is recalled. However, this memorial value is strengthened by a potential value which leads to consider them as open forms, available to encourage the compositional research of contemporary architecture. This double worth, remembering the past and suggesting new transformations, is also intimately bound to the definition of museum. In the ABDR’s project, proposed in 2006, on the occasion of the international consultation for the Mausoleum of Augustus and Piazza Augusto Imperatore, the archaeological ruin re-gains a contemporary sense, becoming itself a museum of the complex palimpsest of the place.